A thermal management system for electric vehicle batteries - Rahman, Mohammed Ataur; Hawlader, Mohammad Nurul Alam (2015)
The present invention relates to a thermal management system for a battery module (102) of a vehicle, comprising a heat exchanger (101) for removing heat from the battery module (102); a heat transfer medium (103); a regulator (104); a temperature sensor (105); a compressor (106); a condenser (107); and characterised by an expansion valve (108) connected to regulator (104) and the inlet of the heat exchanger (101) wherein the expansion valve is provided with a fuzzy logic system for regulating the flow of refrigerant in response to temperature changes in the heat exchanger (101). The present invention also relates to a method for regulating the temperature of the battery module (102) using the thermal management system; and characterised in that the closing and opening of the expansion valve (108) is controlled by the fuzzy logic system in response to a specified temperature range.